2023
DOI: 10.1021/acsanm.3c00464
|View full text |Cite
|
Sign up to set email alerts
|

Se-Doped Magnetic Co–Ni Spinel Ferrite Nanoparticles as Electrochemical Catalysts for Hydrogen Evolution

Abstract: The magnetic Co 0.5 Ni 0.5 Fe 2 O 4 spinel ferrites (NSFs) with various (x%) Se (x = 0.00−0.20) were synthesized via the sol−gel combustion route in conjunction with an advanced green laser ablation method. The structure and morphology of NSFs were explored through various physicochemical techniques. Interestingly, Se doping has a crucial impact on NSFs' magnetic properties. While, at room temperature, the pristine sample exhibits a superparamagnetic-like behavior, the pristine sample and all doped CoNi NSFs +… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(5 citation statements)
references
References 58 publications
1
4
0
Order By: Relevance
“…The ECSA histogram depicted in Figure f indicates that introducing Mo doping into the NiMo x Co 2– x O 4 CNSP electrode results in a considerable increase in ECSA compared to the unmodified NiCo 2 O 4 electrode. The introduction of Mo doping has the potential to alter the electron distribution and impede the surface oxidation of NiCo 2 O 4 , leading to an increase in the availability of active sites and ultimately promoting the efficacy of the HER process . Nevertheless, an overabundance of Mo doping in NiCo 2 O 4 CNSPs could potentially hinder the active sites and function as a recombination center due to alterations in the structure and composition .…”
Section: Resultssupporting
confidence: 75%
See 2 more Smart Citations
“…The ECSA histogram depicted in Figure f indicates that introducing Mo doping into the NiMo x Co 2– x O 4 CNSP electrode results in a considerable increase in ECSA compared to the unmodified NiCo 2 O 4 electrode. The introduction of Mo doping has the potential to alter the electron distribution and impede the surface oxidation of NiCo 2 O 4 , leading to an increase in the availability of active sites and ultimately promoting the efficacy of the HER process . Nevertheless, an overabundance of Mo doping in NiCo 2 O 4 CNSPs could potentially hinder the active sites and function as a recombination center due to alterations in the structure and composition .…”
Section: Resultssupporting
confidence: 75%
“…The Tafel slope has been widely employed to investigate the rate-determining steps in the HER mechanism process for enhanced comprehension. The Volmer, Heyrovsky, and Tafel reactions are widely recognized as the three primary steps involved in converting hydrogen protons into molecular hydrogen. ,,,, Based on the underlying mechanisms, the amalgamation of the Volmer pathway alongside either the Heyrovsky or Tafel pathway could produce molecular hydrogen. Typically, when the slope is approximately 120 mV/dec, the Volmer step mechanism is the reaction rate’s limiting factor.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to better understand the best electrocatalyst (5% WS 2 −MXene) that showed the best activity with respect to its other counterparts, electrochemical surface area (ECSA) and double-layer capacitance (C dl ) were determined. 55 Cyclic voltammetry (CV) in the nonfaradaic region was employed in Figure S(8)at various scan rates ranging from 10 to 100 mV s −1 . The calculated C dl values of 5% WS 2 −MXene, MXene, and WS 2 are presented in Figure 5d.…”
Section: Resultsmentioning
confidence: 99%
“…The incessant rise of environmental pollution, climate change, and energy crises has compelled humanity to seek energy resources that possess abundance, affordability, cleanliness, ecological friendliness, and sustainability. In light of this, hydrogen has emerged as a prospective fuel for the future, offering the potential to address various challenges associated with environmental and energy crises. , It is established that hydrogen can efficiently be produced at low cost via the electrolysis of water, offering a versatile resource of renewable energy like solar and wind . Research revealed that the alkaline electrocatalytic hydrogen evolution reaction (HER) is preferable with acidic and neutral electrolytes because of less corrosion for equipment and transition metal-based electrodes.…”
Section: Introductionmentioning
confidence: 99%